Research the Impact on Stock Index and Stock Index Future under the Trade Policies Adjustment -- Based on China and the US - Le Sihan (SHS Web of Conferences, 2025)
In reset years, many international uncertainties emerge, especially in trade policies. The US announced a higher tariff on imported commodities manufactured in China, Mexico, and Canada on 1 February 2025. The higher trade barrier gives a hint to explore how the uncertain trade policies affect the spot and future market under the case that most countries’ economies are connected tightly in the global market. This research estimates the impact of trade policy uncertainty on the stock index and stock index future. Fitting the VECM model during the influence persisting in the spot and future market and the whole period the research is conducted to test the return spillover effect between the CSI 300 index and the CSI 300 index future. After examining the return of spot and future, there is a spillover effect in the spot and future market, meanwhile, the price discovery of the future still works under the dynamic changes.